Occurrence of Gram-negative bacteria in cockroaches obtained from different areas of Dhaka city - Akter, Tangin; Ahmed, Sangita; Hasanuzzaman, - (Bangladesh Journal of Zoology, 2017)
The presence of Gram-negative bacteria in cuticle and alimentary tract of cockroaches collected from four selected areas of Dhaka city was investigated. Using detection key, a total of 12 cockroaches were identified as Periplaneta americana (58.33%), Blattella germanica (33.33%) and Blatta orientalis (8.33%). From these three species 54 different bacterial isolates were obtained. Out of them, 33 were obtained from P. americana (14 from external and 19 from gut), 9 from B. orientalis (5 from external and 4 from gut) and 12 from B. germanica (5 from external and 7 from gut). Bacterial isolates obtained from external surface of the cockroaches belonged to four different Gram negative bacterial species (Klebsiella spp., Pseudomonas spp., Enterobacter spp. and E. coli), six bacteria have been obtained from alimentary tract (Klebsiella spp, Pseudomonas spp., Enterobacter spp., Escherichia coli, Salmonella spp. and Shigella spp.). Pseudomonas spp. were the most predominant bacteria isolated from external surface (33.34%) while Klebsiella spp. were found to dominate in alimentary tract (23.33%). P. americana carried the highest number (33) of bacterial isolates and B. orientalis carried the minimum (9). This study shows that cockroaches carry several bacteria on their external body surface and alimentary tract and can play a role in bacterial transmission to humans. Therefore, the existence of cockroaches in human dwellings is a serious public health problem. Bangladesh J. Zool. 44(2): 229-236, 2016